KARAKTERISASI ES KRIM EDAMAME DENGAN VARIASI JENIS DAN JUMLAH PENSTABIL - Kamalia Istiqomah; Yhulia Praptiningsih; Wiwik Siti Windrati (Faculty of Agricultural Technology, University of Jember, 2017)
Ice cream is a frozen dessert usually made from dairy products such as milk and often combined with other ingredients which made by freezing and agitation. Edamame can be make to vegetable milk as raw material of ice cream. The production of ice cream need stabilizer to get the good properties of ice cream. The purpose of this research were determine the type and amout of stabilizer to produce the good properties and preference of ice cream. This research conducted by Completely randomized design (CRD) with two factor. The first factor were types of stabilizer ( karagenan and CMC) and the second factor were amount of stabilizer (0,2%; 0,4%;0,6%). The parameter observation were overrun, brightness, melting rate, textur, and preference colour, taste, flavor, texture and overall of ice cream. The best tratment was determined by effectiveness test. The best result was obtained on ice cream with stabililizer CMC 0,4%. The ice cream had overrun 24,51%, brightness 80,30, melting rate 38,01 %/15 minute and texture 11,7 mm/10 seconds and the preference value of colour 4,08 (rather like to like) ; flavour 4,60(netral up to rather like); taste 6,05 (like to very like); texture 6,12 (like to very like); overall 5,84 (rather like to like). Keywords: carrageenan ice cream, edamame, stabilizer, CMC